(3aj VhA eYGjjQ GdJObjb GdOhdjIs - (3NGdO QGZH(B, (3GdNWjHs ((3YeGf(B:s (3OGQ GdHOGjI(B,s, 2009)
(3CSGSjGJ JUeje GdfXGe GdeMGSHj h fXGe GdGJUGd GdeMGSHj h OhQg aj GdQbGHI , GdeYGjjQ GdegfjI dJObjb GdMSGHGJ h GdGSJKeGQGJ GdGLfHjI , fXQjI GdJOhjd , GdYhdeI h JCKjQgG Ydi GdGfXeI GdeMGSHjI GdYQHjI GdehMOI h GfYcGSGJgG Ydi GdGSJKeGQ GdGLfHj GdeHGTQ , hGbY h JMOjGJ GdGSJKeGQGJ GdGLfHjI GdeHGTQI aj GdOhd GdfGejI (B.s
(3eQGLY U(B.233 ((3GbJfGAGJ (B2014 3(3f(B)s
Keywords: (3GdGSJKeGQGJs; (3GdGSJKeGQGJ GdGLfHjIs; (3GdTQcGJ eJYOOI GdLfSjIs; (3JObjb GdMSGHGJs